Community Empowerment Based on Local Wisdom (Study of Globalization Idea in Community Empowerment) - Abdul Ghoni (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2016)
This article provides an overview important concepts of activities and conditions in the environment around ussociologically related qualitative content analysis. In fact, the community is flourishing, can not be separated from the influence of globalization. The use of technology and the jargon of modernity has haunted the community. Whereas the existing development is not always